Diagnostics And Therapy Of Eye Allergic Diseases. - Ibragimova N.N. (Zien Journals, 2025)
This paper represents literature review devoted to most actual ussues of diagnostics and therapy of eye allergic diseases. Information about modern methods of diagnostics of allergic conjunctivitis that used in clinical practice was systemized. Data from clinical tests on different drug groups and their effectiveness was delivered. Also there was performed comparative analysis of therapy plans that prescribed by different authors
Keywords: allergy; allergic conjunctivitis; pollinoses